Sell the brand first - Stiff, Dan (McGraw-Hill, 2006)
Sell the Brand First reveals a fresh, highly effective way to close the sale: by selling to your customers from brand strength. Corporate trainer and brand selling specialist Dan Stiff shares his proven Brand Staircase Method-a four-step process that shows you how to hone in on your customers' mind-sets, create sales pitches based on how your brand fits into your consumers' lifestyles, and fully satisfy the trade buyers' needs and expectations